Pelatihan Pemrograman Arduino menggunakan Wokwi Simulator di SMK Mambaul Ulum Kebomas-Gresik - Khoirunnisaa, Alfi Zuhriya; Hardiyanti, Mega Rahayu (Jurnal Pengabdian Masyarakat (ABDIRA), 2026)
The Arduino UNO microcontroller is a microcontroller widely used by vocational high school students to design Internet of Things-based projects or intelligent systems in the field of industrial automation. However, some obstacles in making projects using Arduino hardware include unstable data communication, signal interference/noise, wiring errors and component compatibility. Therefore, it is necessary to introduce the Wokwi Simulator to minimize the occurrence of these obstacles. The Wokwi simulator is a simulation for creating prototypes using IoT-based Arduino virtually. The use of this simulator can help vocational high school students in designing industrial automation projects virtually, without purchasing electronic components first. The method used is a theoretical explanation of the Wokwi simulator and direct practice in making IoT-based prototypes using the Wokwi simulator in groups. The results of this community service program include increasing the knowledge and skills of vocational high school students in using the Wokwi simulator both in theory and practice. This was obtained from the post-test results of vocational high school students who got an average score of 94.